1982
DOI: 10.1128/jcm.16.5.895-900.1982
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical, microbiological, and immunological observations of a volunteer repeatedly infected with Chlamydia trachomatis

Abstract: A blind volunteer was inoculated in one eye with an isolate of Chlamydia trachomatis in 1961 and followed for 20 years. During this time, many observations were made of his clinical responses to the first inoculation and several subsequent inoculations with the same and other strains, chlamydial shedding, and antibody and cell-mediated immune responses. Evidence is presented that partial resistance to chlamydial eye infection developed during repeated infections and that antibodies, cell-mediated immune reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…While it is possible the enrollees that were negative for EB-specific antibodies could be due to the use of serovars they were not currently infected with, we did observe negativity with enrollees currently infected with E. Serovar specific immunity has been proposed as a mechanism of protection against re-infection of the same serovar [ 98 , 99 ]. However, in a human trachoma infection, serovar cross-reactive antibodies were observed over time [ 100 ] and in the murine model, protection was observed after heterotypic challenge [ 101 ], suggesting serovar-cross reactive antibodies may be present and assist in protection against re-infection.…”
Section: Discussionmentioning
confidence: 79%
“…While it is possible the enrollees that were negative for EB-specific antibodies could be due to the use of serovars they were not currently infected with, we did observe negativity with enrollees currently infected with E. Serovar specific immunity has been proposed as a mechanism of protection against re-infection of the same serovar [ 98 , 99 ]. However, in a human trachoma infection, serovar cross-reactive antibodies were observed over time [ 100 ] and in the murine model, protection was observed after heterotypic challenge [ 101 ], suggesting serovar-cross reactive antibodies may be present and assist in protection against re-infection.…”
Section: Discussionmentioning
confidence: 79%
“…The kernel distribution of mucosal-derived IgG and IgA data ( Fig 1 ) visualized two distinct patient populations: those that significantly neutralized infection, and those that did not. Given that historic human and non-human primate trachoma studies suggest that immunity to Ct is serovar specific [ 37 , 38 ], we next determined if this differential inhibition could be due to differences in the antigen specificity of patient antibodies. Since MOMP, encoded by ompA , comprises the majority of the protein mass of the outer membrane of EBs and is established an immunodominant antigen, we hypothesized that patient antibodies would most efficiently inhibit infection by Ct strains matching that of the current infecting ompA genotype or genogroup.…”
Section: Resultsmentioning
confidence: 99%
“…Re-infection experiments by others showed that antibody responses are narrowly directed against the MOMP of the infecting serovar, which broadens over time to include cross-reactive antibodies until the infection is cleared [ 39 ]. Interestingly, antibodies against the serovar of the primary infection were recalled to a higher level during secondary infection with a different serovar, and antibody responses were directed mainly against the original infecting serovar, even after re-infection with an identical or different serovar [ 37 , 38 ]. Taken together, the results of historic and our own studies suggest that the serovar of the infecting strain can shape the humoral immune response.…”
Section: Discussionmentioning
confidence: 99%